2017
DOI: 10.1007/978-3-319-66179-7_53
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Metabolites in Magnetic Resonance Spectroscopic Imaging Using Machine Learning

Abstract: Magnetic Resonance Spectroscopic Imaging (MRSI) is a clinical imaging modality for measuring tissue metabolite levels in-vivo. An accurate estimation of spectral parameters allows for better assessment of spectral quality and metabolite concentration levels. The current gold standard quantification method is the LCModel -a commercial fitting tool. However, this fails for spectra having poor signal-to-noise ratio (SNR) or a large number of artifacts. This paper introduces a framework based on random forest regr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 8 publications
0
31
0
Order By: Relevance
“…The potential applications of machine learning for metabolite quantification have also been explored by a few research groups. Using a random forest regression Das et al reported the utility of machine learning for the quantification of major metabolite peaks such as Cho, Cr, Glx, mI, and NAA in the simulated and in vivo 1 H‐MRS spectra. Using deep learning Hatami et al reported a CNN that was trained on the time‐domain dataset and capable of quantifying individual metabolites in simulated spectra.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential applications of machine learning for metabolite quantification have also been explored by a few research groups. Using a random forest regression Das et al reported the utility of machine learning for the quantification of major metabolite peaks such as Cho, Cr, Glx, mI, and NAA in the simulated and in vivo 1 H‐MRS spectra. Using deep learning Hatami et al reported a CNN that was trained on the time‐domain dataset and capable of quantifying individual metabolites in simulated spectra.…”
Section: Discussionmentioning
confidence: 99%
“…Given the recent accomplishment of deep learning in a variety of different tasks and its potential application in 1 H‐MRS, we developed a CNN that maps degraded generic in vivo brain spectra at short TE into noise‐free, line‐narrowed, baseline‐removed, metabolite‐only spectra (intact metabolite spectra). The subsequent metabolite quantification from such intact metabolite spectra is achieved by solving a simple inverse problem using a metabolite basis set.…”
Section: Introductionmentioning
confidence: 99%
“…We also compare our results with the only machine learning approach applied on MRS quantification i.e. random forest regression algorithm [5]. However, since the full details on the features used for the random forest is not given, we applied it on the raw data (no traditional hand-crafted feature extraction used).…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…For tFID 1024 (null truncation), the CNN returns the input spectrum as it is. Therefore, our CNN may be combined with another CNN unit that takes part in metabolite quantification, such that those spectra from truncated FIDs are recovered prior to entering the next CNN, whereas those fully acquired spectra simply pass through spec CNN spec . As previously discussed, screening of the quality of the input data is important, such as for minimizing the mentioned possibility of processing the data contaminated by unwanted signal.…”
Section: Discussionmentioning
confidence: 99%